Levels of cardiovascular disease risk factors in Singapore following a national intervention programme - Cutter Jeffery; Tan Bee Yian; Chew Suok Kai (The World Health Organization, 2001)
OBJECTIVE: To evaluate the impact of the National Healthy Lifestyle Programme, a noncommunicable disease intervention programme for major cardiovascular disease risk factors in Singapore, implemented in 1992. METHODS: The evaluation was carried out in 1998 by the Singapore National Health Survey (NHS). The reference population was 2.2 million multiracial Singapore residents, 18--69 years of age. A population-based survey sample (n = 4723) was selected by disproportionate stratified and systematic sampling. Anthropometric and blood pressure measurements were carried out on all subjects and blood samples were taken for biochemical analysis. FINDINGS: The 1998 results suggest that the National Healthy Lifestyle Programme significantly decreased regular smoking and increased regular exercise over 1992 levels and stabilized the prevalence of obesity and diabetes mellitus. However, the prevalence of high total blood cholesterol and hypertension increased. Ethnic differences in the prevalence of diabetes mellitus, hypertension, and smoking; and in lipid profile and exercise levels were also observed. CONCLUSION: The intervention had mixed results after six years. Successful strategies have been continued and strengthened.